MODEL PEMBELAJARAN KOOPERATIF KANCING GEMERINCING UNTUK MENINGKATKAN PEMAHAMAN SISWA PADA MATERI LINGKARAN - Rini Utami (LPPM Universitas Pekalongan, 2013)
Student law achievment in mathematic in SMP Negeri 4 Pekalongan because lack understanding in mathematic, so that new teaching model should be used to improve student’ achievment. One model of learning that can be applied to overcome these problems is kancing gemerincing cooperative learning model. Cooperative learning arises from the concept that student will more easliy find and understand difficult concept if they are dicussing with friends. In the activity kancing gemerincing, each member of the group gets achance to contribute their views and ideas and listen to other members. The place of the research is SMP Negeri 4 Pekalongan . The subject of the research is eight grade students. Class action research with cycle model is used as the method of research. Method of collecting data used in this research is observation and test. data analysis used is descriptive analysis. The result of the research is that teaching using card model can improve students' comprehesion in material of circle. Kata kunci : Kancing Gemerincing Cooperative Learning Model, Action Research, Circle.